Optic neuritis following SARS-CoV-2 infection - Rodríguez-Rodríguez, Mónica Saray (J Neurovirol, 2021)
The most common neurologic symptoms in COVID-19 are headache, anosmia, and dysgeusia. Optic neuritis is an unusual manifestation of SARS-CoV-2 infection. We report a case of a patient who initially consulted for vision loss in the absence of respiratory symptoms. She was diagnosed with optic neuritis following SARS-CoV-2 infection. Delay in diagnosis of neuro-ophthalmic manifestations of COVID-19 may lead to irreversible optic atrophy. A mechanism in which viral antigens would induce an immune response against self-proteins, or direct SARS Cov-2 infection of the central nervous system, may be involved in optic nerve injury.